PERAN PEMERINTAH KOTA SEMARANG DALAM KOORDINASI MULTISEKTORAL PADA IMPLEMENTASI LAYANAN NOMOR DARURAT CALL CENTER 112 DI KOTA SEMARANG - Vincensius Manalu; Hendra Try Ardianto (Journal of Politic and Government Studies, 2020)
This study will provide an overview of how the Semarang City Government inrealizing multisectoral-based coordination of public services where there are many sectors and elements in it. This research will also show the sustainability of multi-sectoral coordination carried out by the Semarang City Government on the Call Center 112 services through various forms of coordination In seeking data, the authors conducted a participatory observation study directly on this service, and also conducted interviews as primary data to the leaders and operators and volunteers involved in this service. Then it will be analyzed through the theory of the role of government according to Fuady and Gunarsa (2010) which divides the role of government into 2 namely facilitators and coordinators, then the writer takes the role of government as executor Whereas in knowing the continuity of coordination that occurs, the writer takes the theory of the form of coordination form that was sparked by Syafiie (2011) 3 which expressed 3 forms of coordination namely horizontal, vertical, and functional as well as the theory of Handayaningrat (in Mahfud 2015) which expressed the form of internal and external coordination The Semarang City Government plays its role in the continuation of coordination in this service, whereby all of these roles are carried out so that the multi-sectoral coordination that is realized becomes ideal, from the existence of such coordination, forming continued coordination which leads to cooperation between elements that have equal or hierarchical positions.Keywords: The role of government, Coordination, Multi – sectoral, Call Center 112